REFORMULASI AKUNTABILITAS KEPALA SEKOLAH UNTUK PENGUATAN MANAJEMEN SEKOLAH DASAR DI ERA DISRUPSI DIGITAL: STUDI KASUS SD IT DARUL HIKMAH PASAMAN BARAT - Rahmawati, Milatul; Hayati, Hazimah Dzikra; Gistituati, Nurhizrah; Anisah, Anisah; Rusdinal, Rusdinal (STKIP Pesisir Selatan, 2025)
The 21st century presents many challenges. Including the world of education, which requires flexible, skilled, and technology-aware human resources. The government, schools, and society form the pillars of HR to answer these problems. The principal, as the smallest community, is responsible for student development in accordance with modern learning requirements. School-based management is a management method based on student involvement. Thus, supporting resources are very important because each educational institution has control over human resources, finances, and the environment. SD IT Darul Hikmah has the ability to adapt to modern school-based management. Having a strategy to manage the institution so that it becomes a reference elementary school for new students and a religious-based literacy school is part of the institution's resources. How does SD IT Darul Hikmah deal with the challenges of human resource development in this century? By using a literacy approach and interviews conducted directly with the principal and teachers as sources, a qualitative descriptive method is used in this paper. The data collected shows that the resources owned by the principal have the ability to act as a leader in the management of Islamic educational institutions.